Can someone help me reduce this? I have no idea what to do with the denominator. :-(
$\displaystyle \frac{4x^4-25}{6x^3-4x^2+15x-10}$
Thank you very much!
Numerator : $\displaystyle {4x^4-25} = (2x)^2-(5)^2 $
Since $\displaystyle a^2-b^2=(a+b)(a-b)$ , you can write
$\displaystyle {4x^4-25}= (2x+5)(2x-5)$
and you have:
Denominator: $\displaystyle 6x^3-4x^2+15x-10 = 2x^2(3x-2)+5(3x-2) = (3x-2)(2x^2+5)$
so you have:
$\displaystyle \frac{4x^4-25}{6x^3-4x^2+15x-10}$ $\displaystyle = \frac{(2x+5)(2x-5)}{(3x-2)(2x^2+5)}$
cancel out the like terms